Effect of Sn on the microstructure and properties of biodegradable Mg-1.0Zn-0.3Zr magnesium alloy - Zhao, Fei; Li, Huan; Yan, Chengqi; Song, Beibei; Mao, Xiangshan (Materials research express, 2024)
In order to prepare a new biodegradable magnesium alloy with high biosafety, better mechanical properties, and lower degradation rate, in this paper, the effect of the non-toxic element Sn (0%∼2%, mass%) on the microstructure, mechanical properties, and corrosion resistance of the Mg-1.0Zn-0.3Zr alloy was investigated using optical microscopy, scanning electron microscopy, x-ray diffraction, tensile testing, and corrosion experiments. The results indicated that the addition of Sn to the alloy resulted in the formation of the Mg 2 Sn phase, which improved the mechanical properties of the alloy. However, a higher concentration of this phase and its continuous distribution along the grain boundaries decreased the alloy’s corrosion resistance. The mechanical properties and corrosion resistance of the alloy exhibited an increasing trend with the increase of Sn content, followed by a decreasing trend. At an Sn content of 1%, the alloy demonstrated better mechanical properties and corrosion resistance simultaneously. The yield strength, tensile strength, and elongation of the alloy were 114 ± 2 MPa, 164 ± 5 MPa, and 13.3 ± 0.1%, respectively. Additionally, the corrosion rate of the alloy was only 0.61 mm y −1 after being immersed in simulated body fluids for 120 h. These properties represent a significant improvement over those of the Mg-1.0Zn-0.3Zr alloy. Our results indicate that the addition of an appropriate amount of Sn element can improve both the mechanical properties and corrosion resistance of the alloy, supporting the development of new biodegradable magnesium alloys.